The Effect of Budgeting on the Financial Performance of Government Organisations: A Case Study of Kaliro District Local Government - Doreen Mwesigwa (Uganda Christian University, 2024)
The study examined how budgeting affects the financial performance of government organizations, focusing on the Kaliro District Local Government. Its objectives included assessing the budgeting process, analyzing the impact of budget monitoring, determining the influence of budget forecasts, and investigating the role of budgetary participation in financial performance. Employing a descriptive cross-sectional design, the research integrated both qualitative and quantitative methods to collect data from 34 respondents, achieving a response rate of 89.6%. Data was gathered through questionnaires and interviews with employees and managers. The analysis utilized the Statistical Package for Social Sciences (SPSS) for quantitative data and content and thematic analysis for qualitative data. The findings revealed a significant connection between accounting information and decision-making, as well as a strong link between the completeness of information and effective decision-making. These outcomes highlight the importance of structured budgeting and participatory approaches in improving financial performance within government organizations.